Crisis management during regional anaesthesia - Fox, M (BMJ Group, 2005)
Background: Regional anaesthesia is widely used and has been considered to pose few risks once the block is established. However, life threatening problems can occur both during the establishment and maintenance phases of a regional block which require prompt recognition and management. Objectives: To examine the role of a previously described core algorithm "COVER ABCD–A SWIFT CHECK", supplemented by a specific sub-algorithm for regional anaesthesia, in the management of problems arising in association with regional anaesthesia. Methods: The potential performance of this structured approach was assessed for each of the relevant incidents among the first 4000 reported to the Australian Incident Monitoring Study (AIMS). Results: There were 252 incidents involving regional anaesthesia, 6.3% of the first 4000 reports to AIMS. Of these, the majority (78%) involved the use of epidural or spinal anaesthesia. The core algorithm AB COVER CD properly applied, would have accounted for 45% of all problems, and is worth applying to eliminate unexpected problems unrelated to the regional anaesthesia technique itself. Hypotension and dysrhythmias made up over 30% of all incidents and accounted for all six deaths in the 252 incidents. The specific sub-algorithm for regional anaesthetic techniques accounted for 55% of all incidents: problems with delivery to the site of action, 49 cases (19%); problems with the block, 30 cases (12%); local anaesthetic toxicity, 30 cases (12%); trauma, infection, or pain, 14 cases (6%), wrong side or wrong patient, five cases (2%). Conclusion: Based on an analysis of 252 incidents, the core algorithm and the regional anaesthesia sub-algorithm, properly applied, would lead to swift recognition and appropriate management of problems arising in association with regional anaesthesia.